2006
DOI: 10.1002/jez.b.21144
|View full text |Cite
|
Sign up to set email alerts
|

PCR survey of hox genes in the goldfish Carassius auratus auratus

Abstract: A tetraploidization event took place in the cyprinid lineage leading to goldfishes about 15 million years ago. A PCR survey for Hox genes in the goldfish Carassius auratus auratus (Actinopterygii: Cyprinidae) was performed to assess the consequences of this genome duplication. Not surprisingly, the genomic organization of the Hox gene clusters of goldfish is similar to that of the closely related zebrafish (Danio rerio). However, the goldfish exhibits a much larger number of recent pseudogenes, which are chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 61 publications
2
28
0
1
Order By: Relevance
“…And, this early polyploidy event might result in an ancestral common tetraploid ancestor of Carassius auratus gibelio, Carassius auratus auratus and Cyprinus carpio. Significantly, the evolutionary history of polyploidy occurrence is basically consistent with the corresponding genome duplication time reported previously in Cyprinus carpio (12 Mya) (David et al, 2003) and in Carassius auratus auratus (15 Mya) (Luo et al, 2007), and with the estimated separation time between Cyprinus carpio and Carassius auratus based on molecular clock of cytochrome b sequences (Gao et al, 2012). After that, the common ancestor should have diverged and differentiated via successive diploidization, and led to the currently diploidized tetraploid Cyprinus carpio and Carassius auratus.…”
Section: A Hypothesized Model For Two Rounds Of Polyploidy Origins Insupporting
confidence: 88%
See 2 more Smart Citations
“…And, this early polyploidy event might result in an ancestral common tetraploid ancestor of Carassius auratus gibelio, Carassius auratus auratus and Cyprinus carpio. Significantly, the evolutionary history of polyploidy occurrence is basically consistent with the corresponding genome duplication time reported previously in Cyprinus carpio (12 Mya) (David et al, 2003) and in Carassius auratus auratus (15 Mya) (Luo et al, 2007), and with the estimated separation time between Cyprinus carpio and Carassius auratus based on molecular clock of cytochrome b sequences (Gao et al, 2012). After that, the common ancestor should have diverged and differentiated via successive diploidization, and led to the currently diploidized tetraploid Cyprinus carpio and Carassius auratus.…”
Section: A Hypothesized Model For Two Rounds Of Polyploidy Origins Insupporting
confidence: 88%
“…In comparison with the prevalent incidence in plants, polyploid species or forms are very rare in vertebrates including fishes and amphibians (Gui and Zhou, 2010;Otto, 2007), but some polyploid members have passed through a bottleneck of polyploidy instability in some teleost fish lineages including cyprinids, catostomids, salmonids, and cobitids, and formed diploid species via diploidization (Allendorf and Thorgaard, 1984;Gui and Zhou, 2010;Saitoh et al, 2010;Yang and Gui, 2004). Therefore, polyploidy has been a vital evolutionary force and plays important roles in fish evolution and speciation (Luo et al, 2007;Mungpakdee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Result of PCR survey of Hox genes in tetraploid goldfish indicated that pseudogene formation caused by deletions is more prevalent, which might be the consequence of dosage effects (Luo et al, 2007). In our analysis, total 202 PCR fragments of Sox genes were sequenced.…”
Section: Evolutionary Behavior Of Duplicated Sox Genementioning
confidence: 99%
“…Brunet et al [26] held that in teleost fishes following duplication, there is an asymmetric acceleration of evolutionary rate in one of two paralogs. Result of PCR survey Hox genes indicated that pseudogene formation caused by deletions in tetraploid goldfish is more prevalent, which may be the consequence of dosage effects as suggested by Luo et al [39] . In our analysis, Sox genes in Tor douronensis don't show the evolutionary pattern as Hox genes in goldfish, although we just obtained partial of Sox gene sequenses in the HMG domain.…”
Section: Sox Gene Diversity In Tor Douronensismentioning
confidence: 92%